Circular Economy Integration in Community-Based Forest Management: A Sustainability Analysis in Indonesia - Hamzah, Baginda; Hasannudin, Dian Ayu Lestari (Jurnal Hutan dan Masyarakat, 2025)
This study examines the integration of circular economy principles into community-based forest management (CBFM) collaborative strategies in Indonesia. Using a systematic literature review methodology, we analyzed 25 published studies and policy documents from 2015-2024, focusing on the interface between circular economy and collaborative forest governance. Results reveal that CBFM initiatives incorporating circular principles show enhanced resource efficiency and increased community income compared to conventional approaches. Four key integration models were identified: closed-loop forest product systems, regenerative agroforestry, waste-to-value conversion, and circular value chain partnerships. Critical success factors include adaptive governance mechanisms, multi-stakeholder knowledge platforms, and policy coherence across sectors. Significant implementation barriers persist, including capacity limitations, misaligned incentive structures, and inadequate market access. The study provides a multi-dimensional analytical framework and strategic recommendations for policymakers and practitioners seeking to advance sustainable forest management through circular economy integration in the Indonesian context.